Spatio-temporal distribution of microplastic pollution in surface sediments along the coastal areas of Istanbul, Turkey - Erkan, Hanife Sari; Takatas, Betul; Ozturk, Alihan; Guendogdu, Sedat; Aydin, Fatih; Koker, Latife; Ozdemir, Oguz Kaan; Albay, Meric; Engin, Guleda Onkal (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Microplastics (MPs) have become prevalent in various environmental compartments, including air, water, and soil, attracting attention as significant pollutant parameters. This study investigated the prevalence of MP pollution in surface sediments along Istanbul's Marmara Sea, encompassing the megacity and the Bosphorus. A comprehensive sampling approach was employed, covering 43 stations across four seasons and depths ranging from 5 to 70 m. The objective was to assess the impact of terrestrial, social, and industrial activities on MPs. The average concentrations varied per season, with fall, winter, spring, and summer values recorded as 2000 +/- 4100, 1600 +/- 3900, 4300 +/- 12,000, and 9500 +/- 20,300 particles/kg-DW. The study identified river stations in the Golden Horn and sea discharge locations as hotspots for high concentrations. Notably, the dominant shape shifted from fibers in fall, winter, and spring to fragments during summer, coinciding with mucilage occurrences. The study identified 11 different polymers, with polyethylene (44 %) and polypropylene (31 %) being the most common.
Keywords: Microplastics; Surface sediment; Mega-city; Istanbul; Marmara Sea; Golden Horn; Spatio-temporal distribution; NORTH YELLOW SEA; WASTE-WATER; MARINE-SEDIMENTS; BEACH SEDIMENTS; PLASTIC LITTER; DEMERSAL FISH; 1ST REPORT; ABUNDANCE; GULF; BAY; Environmental Sciences & Ecology; Marine & Freshwater Biology